(untitled) (International Journal of Environmental Sciences, 2025)
Employee performance is one of the most studied variables considering that employee performance is linked to organizational performance. Social networks at the workplace define the inter relationship between individuals and groups. The ties strength and network composition are two important aspects which provide resources through social networks. Social support is a vital emotional and material source within the organizational set up. Both social networks and social support are addressing the social relationships dynamics at the workplace and are helpful in building social capital. Subjective well-being and its relationship with employee job performance requires more attention. Social relations at work provide emotional and instrumental resources which improve employee happiness directly and indirectly. The overall life satisfaction is contributing to the positive work outcomes for employees. The aim of the present study is to examine if social networks are meaningfully predicting subjective well-being and employee performance. Furthermore, the mediation by subjective well-being between social relationships and employee performance is investigated. The findings of the study indicated that social relationships are significantly predicting subjective wellbeing and employee performance. Subjective wellbeing is significantly mediating the relationship between social relationship and employee performance. The findings of the study advance the literature on social relationships in the organizational settings. The results of the study substantiate further the concept of social networks and at the workplace.